MOSQUITO DISTRIBUTION OF MOSQUITE-DISEASES MALARIA, JAP ANCE ENCEPHALITIS AND FILARIA IN SEVERAL A CENTRAL JAVA AREA - Hasan Boesri; Damar Tri Boewono; Hadi Suwasono; Raharjo Raharjo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
A study on distribution of Malaria, Filariasis, Japanise encephalitis vectors was conducted in several areas of Central Java in 1998/1999. The result showed that larvae of An. barbirostris, An. subpictus, An. aconitus, An. vagus, An. maculatus, An. kochi, Lutzia sp, Cx. vishnui, Cx.pipiens quinquefasciatus,' Cx. gelidus, Lutzia sp Cx. tritaeniorhynchus, Cx. bitaeniorhynchus and Cx. fuscocephalus werefound in the Rice field. Larvae of Ae. Albopictus and Ar. kucingensis were found in the coconut shell. Larvae of Ae. Albopictus and Malaya sp were found in the Banana leaf axil. Larvae of Ae. Albopictus, Ae. aegypti and Cx. pipiens quinquefasciatus werefound in the artificial container. Larvae of Ae. poicilius, and Malaya sp were found in Callocasia leaf axil. Larvae of An. barbirostris, An. vagus, An. subpictus, An. tessellatus, Cx. vishnui, and Mn. uniformis were found in the swamp. Larvae of ex. Pipiens quinquefasciatus were found in the polluted water. Larvae of An.sundaicus, An. subpictus, An. barbirostris and An. vagus werefound in the tick pond. An. maculatus, Ae. albopictus, and An. vagus larvae werefound in the rock pool. Larvae An. barbirostris, Cx. vishnui, and Cx. bitaeniorhynchus of were found in the irrigation canal. Larvae of ex. vishnui, and ex. fuscocephalus were found in the Stream pool. An. barbirostris, ex. fragilis, An. vagus, Cx. Vishnui and Cx. bitaeniorhynchus larvae were found in the pond. Larvae of ex. vishnui were found in the ground pool. Larvae of Ae. albopictus werefound in the Bamboo stump. An. nigerrimus, An. peditaeniatus,. An. vagus, An. subpictus, An. aconitus, An. annularis, An kochi, An. jlavirostris, An. barbirostris, An. indevinitus An. tessellatus, An.maculatus, Cx. bitaeniorhynchus, ex. vishnui, ex. tritaeniorhynchus, Cx. fuscocephalus, Mn. uniformis, Cx.pipiens quinquefasciatus, Cx. gelidus, Mn. uniformis, Ae. poicilius, Ae. subalbatus, and Ar. kuchingensis were found in the cattle shelter during night collection. Based on the information mentioned above showed that the higher area the less of larvae species. Each larval species has a specific breeding site. This data is usefulfor mosquito'control program.